The order of running shoes and how it influences the perception of effort and comfort - Kai Biedermann; Gian-Andri Baumann; Mattia Nolé; Christina M. Spengler; Fernando G. Beltrami (Bern Open Publishing, 2024)
Introduction High performance modern shoes reduce energy expenditure and improve performance, however, these gains may also stem from differences in perceived effort. Humans tend to weigh negative information more heavily than positive information, which could influence perception of effort when different shoes are tested sequentially. This study aimed to determine the existence of negativity bias on different measures of perception when alternating running shoes. Methods Eleven well-trained male athletes [age: 28 ± 6 years, weight: 68 ± 5 kg, height: 179 ± 5 cm, peak oxygen consumption: 65 ± 4 ml O2･kg-1･min-1] performed three lab visits: a familiarization day with an incremental test followed by two experimental days (track and treadmill, in balanced order). On each day, participants performed four sets of two 5-min runs at 16km･h-1 (5-min breaks in-between) alternating between On Cloudrunner (entry-level, EL) and Cloudboom Echo 3 (high-performance, HP). The order of the shoes was changed every set (i.e, EL-HP or HP-EL). After each run, participants reported their perception of effort (both on a 100-mm Visual Analog Scale [VAS] and on a 1-10 Borg Scale) and shoe comfort (VAS). Heart rate and gas exchange were monitored using a chest sensor and a metabolic cart. Differences in ratings between EL-HP and HP-EL were compared using paired t-tests. Results In combined data of track and treadmill, the physiological response and perception of effort were significantly lower while perception of comfort was significantly higher with HP compared to EL. On the treadmill, the absolute value of the change in perceived effort (VAS) was lower for EL-HP compared with HP-EL (0.6 ± 0.5 mm vs. 1.0 ± 0.7 mm, p = 0.013), but not on the track (EL-HP 0.5 ± 0.5 mm vs. HP-EL 0.6 ± 0.3 mm, p = 0.602). Absolute changes of effort (Borg) were neither affected by shoe order on the treadmill (EL-HP 0.7 ± 0.4 pts vs. HP-EL 0.8 ± 0.7 pts, p = 0.699) nor on the track (EL-HP 0.5 ± 0.4 pts vs. HP-EL 0.7 ± 0.6 pts, p = 0.452). Similarly, ratings of shoe comfort were neither affected by shoe order on the treadmill (EL-HP 1.8 ± 1.1 mm vs. HP-EL 1.4 ± 1.0 mm, p = 0.086) nor on the track (EL-HP 1.5 ± 1.1 mm vs. HP-EL 1.6 ± 1.0 mm, p = 0.674). Discussion/Conclusion Changes in perceived effort (VAS) assessed during treadmill running were nearly two times larger when switching from EL to HP than vice-versa, supporting the presence of a negativity bias in this specific condition, which could be related to the higher resolution of VAS scales compared with Borg. Possibly, the lack of negativity bias on the track resulted from an overall reduced rating of effort compared with treadmill, which left less room for differences. These findings suggest that it would be beneficial to include a control shoe worn before and between the tested shoes of interest to mitigate any potential negativity bias in tests when determining perceived effort on a treadmill with different shoes.